PENGEMBANGAN SISTEM PENGUKURAN INDEKS MASA TUBUH DIGITAL MENGGUNAKAN METODE FUZZY LOGIC - dwijotomo; Yoga Saputra; Imam Fahruzi; Sumantri Kurniawan Risandriya (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Body Mass Index (BMI) is one of the indicators used to assess an individual's nutritional status based on body weight and height. However, BMI calculation for hospital patients requires manual physical measurements, making the process inefficient. Therefore, this study proposes a prototype capable of measuring BMI easily through the use of sensors and fuzzy logic computation to improve accuracy and flexibility in BMI assessment. The developed system uses several input variables, namely body weight, height, age, and gender. Fuzzy logic is applied to predict the patient's condition based on BMI values, whether categorized as underweight, normal, or obese. System testing was conducted by comparing the results with conventional methods and evaluations by nutrition experts. The findings show that the fuzzy logic–based digital BMI system can accurately and practically classify body condition. The implementation of this system is expected to assist medical personnel and the general public in performing more comprehensive and precise nutritional status assessments